Evaluation of Perum Bulog's Performance in Controlling Rice Prices in Sinjai Regency - Muh. Nasrul Haq (Pustaka Digital Indonesia, 2022)
This study aims to determine the performance of Perum Bulog in controlling rice prices and the factors that support and hinder rice price control. The data collection method used was by interviewing the employees of Perum Bulog. Interviews with employees of Perum Bulog in Sinjai Regency if there are indications that prices have gone up in the market, which are monitored or reduced directly from the Ministry of Industry and Trade, food security, Bulog and the food task force, to ensure that prices have indeed gone up or not and to find out the factors that support and hinder price control rice with data analysis method used using descriptive analysis. From the research results it is known that what causes the increase in rice prices is the quality and quantity of rice affected by the weather as well as the type and method of using fertilizers, the increase in the cost of goods purchased by the government (HPP), speculation on price increases, the increase in rice production costs. Steps to overcome this Bulog held a market operation to increase the supply of rice in the market. Market operations are an effective step in controlling rice prices, the problem is lack of order in making payments .